Product design and manufacture : selected, peer reviewed papers from the 2011 international conference on applied mechanics, materials and manufacturing (ICAMMM 2011), November 18-20, 2011, Shenzhen, China - Wen, Jiuba (Applied mechanics and materials ;, 2012)
This collection of peer-reviewed papers covers the latest advances in, and applications of: computer-aided design, manufacturing and engineering, innovative design methodologies, advanced manufacturing technologies, equipment manufacturing, automation equipment, and other related topics; making this a definitive guide to these topics. Review from Book News Inc.: Some 120 papers cover computer-aided designs, manufacturing, and engineering; innovative design methodology; advanced manufacturing technology; equipment manufacturing; automation equipment; and related matters. Among specific topics a.